Ethnoveterinary medicine and health management of Pelung Chicken in West Java, Indonesia - INDRAWATI Y. ASMARA; DANI GARNIDA; MARINA SULISYTATI; SAFITRI TEJANINGSIH; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2018)
Asmara IY, Garnida D, Sulisytati M, Tejaningsih S, Partasasmita R. 2018. Ethnoveterinary medicine and health management of Pelung Chicken in West Java, Indonesia. Biodiversitas 19: 1502-1508. Pelung chicken is a race group of chickens. The spread of Pelung chicken is in the district of Cianjur, and now become widespread to several districts in West Java. The spread of Pelung chicken does occur because as a poultry, it is attractive  to people who like to keep the chicken. The chickens are mainly raised as singing chickens. Some studies showed that health-management practices and disease control measures present challenges in maintaining the existence of the chickens. A survey was carried out to determine health management and the use of ethnoveterinary in raising Pelung chickens. Structured questionnaires were used to collect data involving 131 Pelung keepers in four districts in West Java Province including Cianjur, Sukabumi, Bandung and Garut Districts. The data was analyzed using descriptive analysis. The result showed that respiratory diseases such as Snot (Infectious Coryza) and Tetelo (Newcastle Disease) were main diseases for Pelung chickens. Vaccination combined with ethnoveterinary medicines was a common practice for Pelung keepers to prevent and cure chicken diseases. More than five major medicinal plants were found to be used to cure various chicken diseases in which leaves of papaya and turmeric were the most mentioned by respondents. Documentation and investigations regarding plant properties and their applications for Pelung chickens disease cure should be carried in the future. A combination of vaccination, ethnoveterinary medicine and good hygiene are required to control deadly diseases such as Newcastle Disease. Government intervention would be required to improve keepers' skills and awareness in chicken health management.